Computational study of the reactivity of cytosine derivatives. Issue 14 (20th March 2017) - Jerbi, Jihène; Springborg, Michael
Abstract : The aim of the present study is to provide computational insight using dispersion‐corrected density‐functional calculations into the reactivity properties of modified cytosine in the gas phase and in aqueous solution, whereby special emphasis is put on systems that are obtained through demethylation and methylation. Since this field is relatively incipient, our goal is to identify relationships between reactivity and stability for the modified compounds to understand their biological functionalities. Our results show that addition of a methyl, hydroxylmethyl, formyl, or carboxyl group reduces the length of the nearest hydrogen bond between the cytosine–guanine (CG) base pair and increases the length of the longest hydrogen bond of the DNA base pair. © 2017 Wiley Periodicals, Inc. Abstract : DNA demethylation can be both passive and active. The passive process is related to a dilution of the 5hmC during cell divisions, whereas the active process involves successive TET‐mediated conversions of 5‐hmC to 5‐formyl‐cytosine (5fC) and 5‐carboxyl‐cytosine (5caC), both of which can be transformed back to the unmodified cytosine through the base excision repair (BER) mechanism. The role of DNA demethylation in the development of cancer has been studied only little in the past. Therefore, a computational study is useful to identify relationships between reactivity and stability for the modified compounds to understand their biological functionalities.